Charakterystyka związku między zdaniami opisowymi a zdaniami normatywnymi - Jastrzębski, Andrzej (Uniwersytet im. Adama Mickiewicza, Wydział Teologiczny, 2012)
The philosophical problem that is the focus of this article was polemically coined by David Hume and expressed in a Latin phrase: ab esse ad obligare non valet illatio. Thanks to George Moore, this statement entered into the history of philosophy as the naturalistic fallacy. Hume questioned the possibility of deriving ethics from natural law. He was convinced that moral obligation has its roots rather in human emotions. Subsequently both Immanuel Kant in his categorical imperative, and Max Scheler in his material ethics of values, disputed Hume’s statement. In the present article we will try to address the issue of the naturalistic fallacy, which denies the possibility of deriving an „ought” from an „is”, first of all in the field of formal logic. Afterwards, we will analyze the relationship of descriptive and normative statements philosophically, psychologically and, in the end, neuroscientifically – all this in order to answer the question whether there is any possible link between those two types of statements.
Characteristics of the Relationship between Descriptive Sentences and Normative Statements
Keywords: naturalistic fallacy; „is” and „ought”; descriptive sentences; normative sentences